Analisis Beban Kerja dan Kebutuhan Tenaga Perawat dengan Metode Gillies di Instalasi Rawat Inap Ruangan NS 3B Rumah Sakit Grandmed Lubuk Pakam - Nurmala Sari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
This qualitative descriptive study was conducted to analyze the workload and nurse staffing needs in the NS 3B Inpatient Room, which functions as a Class I, II, and III treatment area for general, isolation, and internal medicine patients. The room has a total of 26 beds and is currently staffed by 16 nurses, with 3 to 5 nurses, including the Head of the Room, available per shift. The study results indicate a high workload, as the average working time for NS 3B nurses is 50 hours per week, which exceeds the standard 40 working hours set by the labor department. While the workload is significantly mitigated by the presence of patient families and practicing students, the burden remains substantial.In terms of time proportion, the activities contributing most to the nurses' workload are indirect nursing activities, accounting for 37.91% of the total working time. Direct nursing activities follow closely, consuming 37.61% of their time. The evaluation of nurse staffing requirements, calculated using the Gillies formula, concludes that the NS 3B room requires 19 nurses. Since the currently available workforce is only 16 people, the NS 3B Inpatient Room is experiencing a personnel shortage of 3 nurses.